The Mediating Role of Business Sustainability in the Relationship Between Dynamic Capabilities and Competitiveness: Evidence from a Private Healthcare Clinic in Indonesia - Burhanuddin Burhanuddin (Indonesian Journal of Islamic Economics and Finance, 2025)
This study aims to examine the effect of dynamic capabilities namely sensing capability, seizing capability, and reconfiguring capability on business sustainability and the competitiveness of Ibnu Sina Clinic, Balikpapan City. Furthermore, this study investigates the mediating role of business sustainability in the relationship between dynamic capabilities and competitiveness. A quantitative research design was employed using a survey method, with all employees of Ibnu Sina Clinic serving as respondents. The collected data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings reveal that dynamic capabilities exert a positive and significant effect on both business sustainability and competitiveness. Moreover, business sustainability is confirmed to mediate the relationship between dynamic capabilities and clinic competitiveness. These results highlight that the organizational ability to sense opportunities, seize them effectively, and reconfigure resources adaptively constitutes a critical determinant of business sustainability and competitive advantage in private healthcare clinics. This study contributes to the dynamic capability literature and offers practical implications for healthcare service management.